Development of Multifunctional Biopolymeric Auto-Fluorescent Micro- and Nanogels as a Platform for Biomedical Applications - Vashist, Arti; Atluri, Venkata; Raymond, Andrea; Kaushik, Ajeet; Parira, Tiyash; Huang, Zaohua; Durygin, Andriy; Tomitaka, Asahi; Nikkhah-Moshaie, Roozbeh; Vashist, Atul; Agudelo, Marisela; Chand, Hitendra S.; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
The emerging field of theranostics for advanced healthcare has raised the demand for effective and safe delivery systems consisting of therapeutics and diagnostics agents in a single monarchy. This requires the development of multi-functional bio-polymeric systems for efficient image-guided therapeutics. This study reports the development of size-controlled (micro-to-nano) auto-fluorescent biopolymeric hydrogel particles of chitosan and hydroxyethyl cellulose (HEC) synthesized using water-in-oil emulsion polymerization technique. Sustainable resource linseed oil-based polyol is introduced as an element of hydrophobicity with an aim to facilitate their ability to traverse the blood-brain barrier (BBB). These linseed oil-based polyol nanogels are demonstrated to have salient features such as biocompatibility, stability, high cellular uptake by a variety of host cells, and ability to transmigrate across an in vitro BBB model. Interestingly, these unique nanogel particles exhibited auto-fluorescence at a wide range of wavelengths 450 - 780 nm on excitation at 405 nm whereas excitation at 710 nm gives emission at 810 nm. In conclusion, this study proposes the developed bio-polymeric fluorescent micro- and nano- gels as a potential theranostic tool for central nervous system (CNS) drug delivery and image-guided therapy.